2011
DOI: 10.1073/pnas.1107573108
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the recoverable high-pressure iron oxide Fe4O5

Abstract: Phases of the iron–oxygen binary system are significant to most scientific disciplines, directly affecting planetary evolution, life, and technology. Iron oxides have unique electronic properties and strongly interact with the environment, particularly through redox reactions. The iron–oxygen phase diagram therefore has been among the most thoroughly investigated, yet it still holds striking findings. Here, we report the discovery of an iron oxide with formula Fe 4 O 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
86
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(90 citation statements)
references
References 37 publications
3
86
1
Order By: Relevance
“…Because the composition of the actual phase present is approximately (Mg 0.5 Fe 0.5 )Fe 2 O 4 , it is not clear whether the phase of this composition would crystallize at extreme pressures in the CaMn 2 O 4 structure (like pure magnesium ferrite, MgFe 2 O 4 ) (Andrault and Bolfan-Casanova, 2001;Levy et al, 2004;Winell et al, 2006), or whether the situation might be more complicated. Recent work has shown that pure magnetite decomposes into a mixture of Fe 2 O 3 (hematite) and the newly-discovered Fe 4 O 5 structure (Lavina et al, 2011;Woodland et al, 2012). Fig.…”
Section: Composition and Structure Of The Magnesioferrite Phasementioning
confidence: 98%
“…Because the composition of the actual phase present is approximately (Mg 0.5 Fe 0.5 )Fe 2 O 4 , it is not clear whether the phase of this composition would crystallize at extreme pressures in the CaMn 2 O 4 structure (like pure magnesium ferrite, MgFe 2 O 4 ) (Andrault and Bolfan-Casanova, 2001;Levy et al, 2004;Winell et al, 2006), or whether the situation might be more complicated. Recent work has shown that pure magnetite decomposes into a mixture of Fe 2 O 3 (hematite) and the newly-discovered Fe 4 O 5 structure (Lavina et al, 2011;Woodland et al, 2012). Fig.…”
Section: Composition and Structure Of The Magnesioferrite Phasementioning
confidence: 98%
“…Among them, FeO and Fe 2 O 3 are two end members and the most well-known compounds. However other kinds of iron oxides with new stoichiometry, such as Fe 4 O 5 [2] and Fe 5 O 6 [3], are also discovered under the high pressure and temperature. Recently FeO 2 , which holds an excessive amount of oxygen, is identified with both first-principles calculation and experiment near 76 GPa [1].…”
mentioning
confidence: 99%
“…The high-pressure Fe-oxide, Fe 4 O 5 is stable from 5 to at least 30 GPa, and is recoverable to ambient conditions (Lavina et al 2011). They synthesized Fe 4 O 5 in a pure Fe-O system, using mixtures of Fe and Fe 3 O 4 as starting material, at P = 10 and 20 GPa, and T between 1227 and 1927 °C and refined the structure as isostructural with CaFe 3 O 5 (space group Cmcm).…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of the high-pressure Fe-oxide Fe 4 O 5 (Lavina et al 2011) (Hazen and Jeanloz 1984). It crystallizes in the cubic NaCl-type structure and forms a solid solution series with MgO (periclase).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation